BIOPESTICIDAL ACTIVITY OF Calotropis procera L. AGAINST Macrophomina phaseolina - Waheed, Nidra; Jabeen, Khajista; Iqbal, Sumera; Javaid, Arshad (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Mungbean [Vigna radiata (L.) Wilczek] is an important pulse crop globally. This imperative crop is severely affectedby charcoal rot disease caused by Macrophomina phaseolina (Tassi) Goid. In the present study, the leaves of Calotropis procera L.were tested for their antifungal potential against M. phaseolina.Materials and Methods: Various concentrations i.e. 1%, 2.5%, 4%, 5.5% and 7% of methanolic extract of C. procera leaves wereprepared and their in vitro bioactivity was examined against the test fungus. Methnolic leaf extract was partitioned using n-hexane,chloroform, ethyl acetate and n-butanol and antifungal activity of each fraction was evaluated. n-Hexane fraction was subjected toGC-MS analysis.Results: The higher concentration of methanolic leaf extract (7%) caused maximum inhibition in the diameter of M. phaseolina i.e.38%. The n-hexane fraction of methanolic leaf extract was found to be the most effective against M. phaseolina. Seven compoundsbelonging to classes of chlorocarbon, aromatic hydrocarbon, azocompounds, aromatic carboxylic acids and fatty acids wereidentified in GC-MS analysis of n-hexane fraction.Conclusion: Antifungal activity of the methanolic leaf extract of C. procera might be due to the presence of the identifiedcompounds in n-hexane fraction of methanolic leaf extract.